ANALYSIS OF FACTORS THAT CAN INFLUENCE CORPORATE SOCIAL RESPONSIBILITY (CSR) WITH EFFECTIVENESS OF THE AUDIT COMMITTEE AS A MODERATING VARIABLE IN PT BANK SUMUT - tania, novi (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to find out and to analyze the influence of Profit Management, Firm Size, Return on Equity, Return on Assets, Non-Performing Loans, Loan to Deposits Ratio, Net Interest Margin, Leverage, and Capital Adequacy Ratio  on CSR (Corporate Social Responsibility) at PT Bank Sumut simultaneously and partially and whether the Effectiveness of Audit Committee could moderate the correlation of Profit Management, Firm Size, Return on Equity, Return on Assets, Non-Performing Loans, Loan to Deposits Ratio, Net Interest Margin, Leverage, and Capital Adequacy Ratio with CSR at PT Bank Sumut. The research used causal comparative method. The population was 25 Branch Offices of PT Bank Sumut in each district/town in North Sumatera which carried out CSR program. The samples were taken by using census sampling technique. The result of the research showed that, simultaneously,   Profit Management, Firm Size, Return on Equity, Return on Assets, Non-Performing Loans, Loan to Deposits Ratio, Net Interest Margin, Leverage, and Capital Adequacy Ratio had significant influence on CSR. Partially, Profit Management had significant influence on CSR, Firm Size had significant influence on CSR, Return on Equity did not have any significant influence on CSR, Return on Assets had significant influence on CSR, Non-Performing Loans did not have any significant influence on CSR, Loan to Deposits Ratio had significant influence on CSR, Net Interest Margin had significant influence on CSR, Leverage did not have any significant influence on CSR, and Capital Adequacy Ratio had significant influence on CSR at PT Bank Sumut. The effectiveness of Audit Committee was not moderating variable which moderated the correlation of Profit Management, Firm Size, Return on Equity, Return on Assets, Non-Performing Loans, Loan to Deposits Ratio, Net Interest Margin, Leverage, and Capital Adequacy Ratio with CSR at PT Bank Sumut.